2007
DOI: 10.1111/j.1399-0012.2006.00635.x
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐drug resistance gene‐1 (MDR‐1) haplotypes and the CYP3A5*1 genotype have no influence on ciclosporin dose requirements as assessed by C0 or C2 measurements

Abstract: The intestinal efflux pump P-glycoprotein (P-gp), the product of the multi-drug resistance-1 (MDR-1) gene, significantly influences the pharmacokinetics of several drugs. Ciclosporin is a substrate for P-gp and is metabolized by cytochrome P450 (CYP) 3A enzymes. P-gp activity is affected by several known single nucleotide polymorphisms (SNPs) and haplotypes. MDR-1 genotypes of SNPs C1236T, G2677T/A and C3435T, as well as haplotypes C-G-C and T-T-T and CYP3A5*1 genotype (predictive of CYP3A5 expression), were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 19 publications
(27 reference statements)
1
17
0
Order By: Relevance
“…This haplotype analysis was done to evaluate the in vivo effects of individual mutations because of the close linkage disequilibrium among the four ABCB1 SNPs. This was consistent with the recent results of Fredericks et al [26] who concluded that ABCB1 haplotypes have only a minor influence on CsA daily dose and dose-adjusted trough levels.…”
Section: Discussionsupporting
confidence: 93%
“…This haplotype analysis was done to evaluate the in vivo effects of individual mutations because of the close linkage disequilibrium among the four ABCB1 SNPs. This was consistent with the recent results of Fredericks et al [26] who concluded that ABCB1 haplotypes have only a minor influence on CsA daily dose and dose-adjusted trough levels.…”
Section: Discussionsupporting
confidence: 93%
“…All included studies were published from 2003 to 2009, of which seven were performed on Asian patients [30][31][32][34][35][36][37][38], three on Caucasian patients [27][28][29], one on North Indian patients, and others did not present any information on ethnicity of the patients. In addition, all the publications were retrospective cohort studies and did not adopt blind design, thus affecting the quality of meta-analysis [26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Furthermore, different studies evaluated the effect of the CYP3A5*3 variant on CsA dose-adjusted C 0 in renal transplant patients at different time points posttransplantation.…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 97%
“…Thirty-three publications were excluded for the following reasons: n = 26, inclusion criterion was unmet; n = 5, dates of the studies were not provided; and n = 2, duplicate citation or the same recipients were described in more than one publication. As a result, 14 clinical studies [26][27][28][29][30][31][32][33][34][35][36][37][38][39] with 1821 renal transplant recipients were included as summarized in Table 1 because they met our preset inclusion criteria of meta-analysis. All included studies were published from 2003 to 2009, of which seven were performed on Asian patients [30][31][32][34][35][36][37][38], three on Caucasian patients [27][28][29], one on North Indian patients, and others did not present any information on ethnicity of the patients.…”
Section: Study Inclusion and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of conflicting reports regarding the CYP3A genotype influence on cyclosporine pharmacokinetic [27,28]. Therefore, a clear role of this polymorphism on cyclosporine metabolism has not been demonstrated.…”
Section: Cyp3a5 and Abcb1 Genotypes And Cyclosporinementioning
confidence: 99%